Odsłonić – udostępnić – uczytelnić. Dziedzictwo kulturowe in situ ‒ przykład ruiny zamku biskupów krakowskich w Iłży - Zapłata, Rafał (Folia Praehistorica Posnaniensia, 2024)
The text refers to issues from the border of museology (in the open air), as well as archaeology and historic architecture. The aim of the article is to provide an introductory discussion of contemporary problems and issues related to revealing, making available and making readable cultural heritage – especially immovable historic objects, including architectural monuments and their subsurface elements – in situ, in the open air. The article is a voice in the discussion on the forms and methods of exhibiting cultural heritage in situ, with reference to the example of the ruins of the castle of the Crakow bishops in Iłża, in particular to those elements of historic buildings that are gradually being uncovered by archaeological research.